Amitosis, including nucleolar behaviour during fragmentation, in both axial and cortical cells of Chara contraria (Charales, Charophyta) - Vouilloud, Amelia Alejandra Beatriz; Caceres, Eduardo Jorge; Leonardi, Patricia Ines (Phycologia)
The results from the present study indicate that in Chara contraria the morphology of amitotic resting nuclei and amitosis depend essentially on the cell type as well to on some extent on the age and development of the cells. Young axial cells of principal axes and branches exhibited C-shaped resting nuclei. During amitosis nuclei initially stretched out and became helical shaped, and they then divided themselves into two similar C-shaped nuclei that remained close to each other. The nucleolar material gradually merged together to eventually form a central nucleolus, which adopted the curving of the nucleus. Spindle-shaped resting nuclei with numerous and irregularly distributed ovoid nucleolar structures were also observed. They duplicated their length during amitosis, underwent a constriction in the middle portion, and finally broke obliquely giving rise to two daughter nuclei, both with similar size. Young corticating cells exhibited initially ovoid nuclei. Then, they gradually stretched out concomitantly with the extension of the cells, giving rise to worm-shaped nuclei that bent irregularly and eventually divided themselves by constriction in portions of different sizes. The ultrastructure of amitotic nuclei in corticating cells was studied. The nuclear envelope remained intact in dividing nuclei. In section, resting nuclei exhibited numerous, small nucleolar profiles homogeneously distributed. In dividing nuclei, in contrast, few, large nucleolar profiles occupied the middle portion of the nucleus. Bundles of 3–66 tubular elements c. 20 nm in diameter ran approximately parallel to the long axis of the nucleus. Tubules were made of circular subunits c. 2 nm in diameter in cross section, and frequently they contacted nucleolar profiles and the inner membrane of the nuclear envelope. Fil: Vouilloud, Amelia Alejandra Beatriz. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia; Argentina Fil: Caceres, Eduardo Jorge. Universidad Nacional del Sur. Departamento de Biología, ...